The Centre–Periphery Antagonism in Adjudication: A Case Study on the Spatial Dimension of the Political - Mańko, Rafał (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
One of the key elements of the critical theory of adjudication is the identification of an objective antagonism that is at stake behind a given court case. The identification of the antagonism allows to develop an axis, along which interpretive possibilities can be spread and arranged from those most favourable to social group A (e.g. workers) to that most favourable to social group B (e.g. businesses). The paper discusses the famous Laval–Viking case-law which was concerned with the fundamental rights of workers (right to strike and undertake collective action) and their relation to the economic freedoms of businesses, seeking to escape the high standards of worker protection in their own country either by changing the flag of a ship to a flag of convenience (Viking) or by importing cheap labour force from abroad, without guaranteeing the workers equal rights (Laval). Whereas the vast majority of scholars have interpreted the Viking–Laval jurisprudence as relating to the fundamental socio-economic antagonism opposing workers and businesses, the Slovenian scholar Damjan Kukovec has proposed an alternative reading. According to him, the real antagonism is ultimately between workers from the periphery (Central Europe, in casu Baltic countries) and workers from the centre (Western Europe, in casu Scandinavian countries). By introducing the spatial dimension to the political, Kukovec entirely changes the formulation of the underlying antagonism. The paper engages critically with Kukovec’s analysis and argues that the objective interest of Central European workers lies not in selling their labour at dumping prices, but gaining the same guarantees of social protection as existing in the West.